Understanding Mucormycoses in the Age of “omics” - Soare, Alexandra Y.; Watkins, Tonya N.; Bruno, Vincent M. (Frontiers in Genetics, 2020)
Mucormycoses are deadly invasive infections caused by several fungal species belonging to the subphylum Mucoromycotina, order Mucorales. Hallmarks of disease progression include angioinvasion and tissue necrosis that aid in fungal dissemination through the blood stream, causing deeper infections and resulting in poor penetration of antifungal agents to the site of infection. In the absence of surgical removal of the infected focus, antifungal therapy alone is rarely curative. Even when surgical debridement is combined with high-dose antifungal therapy, the mortality associated with mucormycoses is >50%. The unacceptably high mortality rate, limited options for therapy and the extreme morbidity of highly disfiguring surgical therapy provide a clear mandate to understand the molecular mechanisms that govern pathogenesis with the hopes of developing alternative strategies to treat and prevent mucormycoses. In the absence of robust forward and reverse genetic systems available for this taxonomic group of fungi, unbiased next-generation sequence (NGS)-based approaches have provided much needed insights into our understanding of many aspects of Mucormycoses, including genome structure, drug resistance, diagnostic development, and fungus-host interactions. Here, we will discuss the specific contributions that NGS-based approaches have made to the field and discuss open questions that can be addressed using similar approaches.